Hubungan antara pemindahan latihan dengan faktor individu dan persekitaran kerja : satu kajian kes di TNB kawasan Johor Bahru, Johor - Abdul Rahman, Noor Hazami (2004)
The purpose of this study was to identify the relationship between individual factor and work environment on the transfer of training. The respondent were 130 employees of TNB Johor Bahru area, who have attended technical courses held between the year of 2001 to 2004 at the Sultan Ahmad Shah Training Institute (ILSAS) Bangi, Selangor. The degree of training transfer and the factors influencing the training transfer were investigated through questionnaire. The data analyses showed that transfer of training were at high level of 69.2%. Pearson Correlation Analysis was used to determine the strenght of the relationship between each dependent variable and independent variables. The finding showed that individual factors and work environment were positively related to the training of transfer. Work environment was the most dominant factor which influenced the transfer of training. It contributed 21.2% towards the transfer of training. The most influential factor for the transfer of training identified by the respondents was the opportunity to use the learned knowledge and skills on the job.